Perbedaan Gaya Pengambilan Keputusan Konsumen antara Konsumen Mahasiswa yang Berbelanja Apparel Product secara In-store dan Online - Karlina Mustika Destianti; Bertina Sjahbadhyni (Jurnal Ilmiah Psikologi MIND SET, 2012)
The increase of online shopping in Indonesia makes the marketing division needs to know the effective technique which may be different with in-store marketing technique. One of the ways to know marketing technique type is through the consumers' decision-making style. This research goal is to see the difference of the decision making type in those selling places, (in-store and online), especially for apparel products. Decision-making style can be known through Consumer Styles Inventory (Sporal & Kendal, 1986). The participants in the research were 110 college students in Jabodetabek area which consist of 55 participants who chose to buy the product online. According to independent sample-test statistics calculation, it is known that there is a significant difference in the quality awareness (the significant score = 0.002, p<0.05). Those who bought the product online were more aware on the quality of the product than those who bought in-store. Therefore, the marketing division should show the products quality to online consumers more than to the in-store consumers so that the marketing will be more effective.